Light Microscopic and Ultrastructural studies on the Preputial Gland of Albino Rat (Rattus Norvegicus) - Bindu, M.; Kishore, P. V.S.; Raju, N. K.B.; Nagamalleswari, Y.; Sreenu, Makkena (Indian Journal of Veterinary Anatomy, 2016)
The preputial gland, the additional paired accessory sex gland in the rat, was a compound alveolar gland of the holocrine type. The parenchyma had lobes of various sizes which consisted of densely packed acini of various types in different sizes and in various states of activity representing the cycle of sebum formation. Small acini with little cytoplasm, rounded acini with a layer of flattened peripheral cells, enlarged acini composed of hypertrophied, vacuolated cells and acini with cellular degeneration and a distinct lumen were observed. The gland was not associated with the hair follicle and the main excretory duct emptied directly onto the skin surface into the area between the inner surface of the prepuce and glans penis. Ultrastructural study revealed cells in different phases of secretory activity. Small and rounded acinar cells with little cytoplasm to intermediate and large acinar cells with the cytoplasm showing the different constituents were observed. The cytoplasm of most of the cells contained several small secretory granules and small to large lipid droplets. Well developed endoplasmic reticulum both agranular and granular along with numerous golgi complexes were observed. The large cells had spherical nuclei with evenly dispersed euchromatin along with peripheral heterochromatin.